2020
DOI: 10.31436/ijohs.v1i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of malocclusion: A review

Abstract: Malocclusion is one of the most common craniofacial problems observed worldwide. Affected individuals suffer not only from aesthetic concerns but also from functional problems, such as with mastication and pronunciation. The prevalence of malocclusion in East Asians is higher than in other races. Reports have shown besides environmental factors, there is association between certain types of malocclusion with specific genes. Positive association of mandibular prognathism has been implicated to genes such as Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…It has been suggested that genetic investigations concerning Class II and I malocclusion are scarce and characterized by small sample sizes, uncertainty regarding the generalizability of findings to populations of diverse ancestries, and narrow trait definitions that overlook the intricate phenotypic spectrum of malocclusion (George et al, 2021). Previous studies have identified several gene candidates as genetic contributors to skeletal malocclusion class II and III (some reviewed in: (Subono et al, 2021, Doraczynska-Kowalik et al, 2017, Mokhtar et al, 2020). Across various ethnicities, studies have suggested that genes correlated with mandibular prognathism are situated in different loci.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that genetic investigations concerning Class II and I malocclusion are scarce and characterized by small sample sizes, uncertainty regarding the generalizability of findings to populations of diverse ancestries, and narrow trait definitions that overlook the intricate phenotypic spectrum of malocclusion (George et al, 2021). Previous studies have identified several gene candidates as genetic contributors to skeletal malocclusion class II and III (some reviewed in: (Subono et al, 2021, Doraczynska-Kowalik et al, 2017, Mokhtar et al, 2020). Across various ethnicities, studies have suggested that genes correlated with mandibular prognathism are situated in different loci.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has shown that genetic factors contributed to the susceptibility to malocclusion. 8 However, both patients were still in their growth period, so it was still possible to perform treatment without invasive procedures, such as extraction or surgery. If treatment were not immediately carried out, it would result in more severe skeletal abnormalities, and if it passed the growth stage, correction of the anterior crossbite would be more difficult and might even require combined orthodontic treatment and orthognathic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Both for Class II and Class III malocclusions, recent studies assessed correlations between phenotypes and the increasing number of polymorphic loci in candidate genes involved in the growth and development of the structures of the craniofacial complex (EPB41, SSX21P, PLXNA, COL2A1, TGFB3, and LTBP2, to name only few, for Class III [20], and FGFR2, MSX1, MATN1, MYOH1, ACTN3, GHR, KAT6B, HDAC4, and AJUBA for Class II [21]). Molecular pathways implicated in the development of bone (TGFB3, LTBP, KAT6B) and cartilage (GHR, Matrilin-1) have been identified as contributing factors to mandibular size discrepancies and Class III malocclusions characterized by variations in mandibular height and prognathism [5].…”
Section: Introductionmentioning
confidence: 99%